Assessing the Impact of Paid Media on Student Enrollment Decisions in Croatian Higher Education: A Comparative Analysis of Media Types - Marjanović, Boris; Košara, David (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Communication is essential in marketing, connecting organizations with their target audiences. However, not all media types hold equal value in customer decision-making. This exploratory study examines the relevance and frequency of use of paid, owned, and earned media in higher education from students’ perspectives. The focus is on paid media due to its high costs and its role in influencing prospective students’ choices. The findings show that owned media are the primary source of information, while paid and earned media play lesser roles. These insights can guide higher education institutions in optimizing communication expenses and improving audience engagement.